Curcumin Aattenuates the Expression of Metalloprotease (AHA_0978) and Serine Protease (AHA_3857) Genes in Aeromonas Hydrophila: Curcumin on Protease Genes in A. Hydrophila: Curcumin on Protease Genes in A. Hydrophila - SobhZahedi, Mahdieh; Zamani, Hojjatollah; YektaKooshali, Mohammad Hossein (Galen Medical Journal, 2023)
Background: Aeromonas hydrophila is a pathogenic bacterium responsible for various infections in humans and animals. Bacterial exoproteases are considered an important determinant in the pathogenicity of A. hydrophila. Serine protease and metalloprotease, that are regulated by the bacterial Quorum sensing (QS) system are important virulent factors in the pathogenicity of A. hydrophila. Anti-QS potential of curcumin has been reported, previously. In this work, we characterized the effect of curcumin on the expression of the metalloprotease and serine protease genes in A. hydrophila. Materials and Methods: The minimum inhibitory concentration (MIC) of curcumin was measured by the agar macro-dilution method and a sub-inhibitory concentration (1/2 MIC) was used in subsequent experiments. The expression level of the metalloprotease and serine protease genes among the treated and control bacteria was evaluated using quantitative PCR (qPCR) assay. Bacterial proteolytic activity was also measured by skim milk agar plate assay. Results: MIC of curcumin for bacterial strain was 1024 μg/ml curcumin, and at 512 µg/mL (1/2 MIC) it remarkably attenuated the expression of the metalloprotease and serine protease genes up to 66 and 77%, respectively. Also, the proteolytic activity of A. hydrophila was considerably reduced by curcumin. Conclusion: Due to the promising inhibitory effect on bacterial proteolysis, curcumin could be considered an anti-virulence agent against A. hydrophila.